Biomechanical Response of the Lower Extremity to Running-Induced Acute Fatigue: A Systematic Review - Apte, Salil; Prigent, Gäelle; Stöggl, Thomas; Martínez, Aaron; Snyder, Cory; Gremeaux-Bader, Vincent; Aminian, Kamiar (Frontiers in Physiology, 2021)
Objective: To investigate: i) The typical protocols used in the research on biomechanical response to running induced fatigue ii) The effect of sport-induced acute fatigue on the biomechanics of running and functional tests iii) The consistency of analyzed parameter trends across different protocols Methods: Scopus, Web of Science, Pubmed, and IEEE databases were searched using keywords and terms identified with the PiCo framework. The studies were screened following the PRISMA guidelines and appraised using the MINORS index. Only studies with fatigue evaluation during and immediately after the fatiguing run were included. Each study was summarized to record information about the protocol and the parameter trends. Summary trends were computed for each parameter based on the results found in individual studies. Results: Of the included 68 studies, a majority were based on in-lab (77.9%) protocols, endpoint measurements (66.8%), stationary measurement systems (76.5%) and treadmill environment (34%) for running. From the 42 identified parameters, in response to acute fatigue, cadence, flight time, contact time, vertical stiffness, knee flexion angle at initial contact, trunk flexion angle, peak tibial acceleration, CoP velocity during balance test showed an increasing behaviour and knee extension force during MVC, maximum vertical ground reaction forces, and CMJ height showed a decreasing trend across different fatigue protocols. Conclusion: The current review presents evidence that acute fatigue influences almost all the included biomechanical parameters, with crucial influence from the exercise intensity and the testing environment. Results indicate an important gap in literature due to the lack of field studies with continuous measurement, conducted during actual sporting activities. Based on this, a wearable inertial sensor-based setup was proposed to address the research gap of continuous assessment of acute fatigue in field.